Journey of Offshore Wellhead Platform Reuse Project - Hutangkura, Nontiwat; Putchakarn, Witthayakom (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 25, 2020)
Several Wellhead Platforms (WHPs) operated by Chevron Thailand Exploration and Production., Ltd. (CTEP) in the Gulf of Thailand are approaching the end of well depletion life. With effective asset integrity management program, most of WHPs are still in good condition. Therefore, an initiative of reused existing WHP topsides, jacket and partial pile sections instead of new procurement and fabrication the whole WHP becomes attractive opportunity as it can enable marginal economic projects, support energy conservation and minimize waster from decommissioning. The 1st pilot project on Topsides reuse was successfully performed in 2017 by relocating pre‐cut Topsides from its jacket and placing on top of new jacket executed by a heavy lifting barge. In 2018, the 2nd campaign for 3 Topsides reuses was executed successfully. After topside reuse project has been executed successfully. The total reuse concept was continued to explore the opportunity and expand the scope of Reuse project. With this initiative challenge, it would be the first ever conventional fixed WHP to be totally reused and relocated to continue its production at the new site which may create more alternatives and opportunities on reuse of existing assets in oil & gas industry. To overcome unforeseen challenges, a conceptual study following with FEED was performed starting in Q2’17 to test on operational constraints, engineering concept, constructability and high-level commercial evaluation. A fatigue analysis is another key study apart from other constructability analyses. Referring to FEED results in Q1’18 with project assurance process from internal Subject Matter Experts and external 3rd party engineering consultant, it can be concluded that total WHP reuse innovation is “technically feasible” and “commercially attractive” without any major project risk.